Interaction Between Hydrogen Sulphide (H2s) And Nitric Oxide (No) In Left Ventricular Hypertrophy And Their Effect On Responsiveness Of Alpha I-adrenergic Receptors Subtypes In The Rat Kidney - Ahmad, Ashfaq (2016)
The present study investigated the effect of left ventricular hypertrophy (LVH) on the responsiveness of (II-adrenergic receptor subtypes to adrenergic stimuli in the rat. The role of hydrogen sulphide (H2S) and nitric oxide (NO) systems and their interaction in the progression of LVH was studied by examining the effect of altered expression of cystathione y lyase (CSE mRNA) and endothelial nitric oxide synthase (eNOS mRN A) in the heart during LVH. Cardiovascular parameters such as cardiac geometry, oxidative stress, arterial stiffness and vascular responsiveness to vasoactive stimuli were studied. In addition, this study examined renal excretory functions, haemodynamics and histopathological changes after exogenous administration of NaHS, an H2S donor, L-arginine, an NO donor and a combination of NaHS and L-arginine. Wistar-Kyoto (WKY) rats were divided into two major groups of Control and LVH. These groups were then subdivided into 8 groups based on treatment. NaHS (56JlM/kg I.P. for 5 weeks) or L-arginine (1.25g1L for 5 weeks in drinking water) treated control or LVH groups. LVH was induced using isoprenaline (Smg/kg, S.c. every 72 hours for 2 weeks) and caffeine (62mglL in drinking water for 2 weeks). The uj-adrenergic receptors subtypes was studied by examining the responsiveness to noradrenaline (NA), phenylephrine (PE) and methoxamine (ME) in the presence of a background intrarenal infusion of selective uj-adrenergic receptors blockers (5-methylurapidil (5-MeU), chloroethy1clonidine (CEC) and BMY 7378). Real-time quantitative peR data (normalized to